An Ethnobotanical Study of the Medicinal Plants Used as Anti-Inflammatory Remedies in Gampaha District, Western Province, Sri Lanka - Mayuri Tharanga Napagoda; Thamudi Sundarapperuma; Diroshi Fonseka; Sachinthi Amarasiri; Prabath Gunaratna (Scientifica)
The application of traditional medicinal plants as anti-inflammatory remedies has been practiced in Sri Lanka for thousands of years. Although there is a rich reserve of indigenous knowledge of medicinal plants, the preservation and the scientific validation of these claims are still in its infancy. Thus, the study was carried out in one of the administrative areas of Sri Lanka known as Gampaha District to assess the significance and contribution of medicinal plants in inflammatory conditions. The data were collected through semistructured and open-ended interviews from 458 volunteers. Ethnobotanical data were analyzed using the relative frequency of citation (RFC), family importance value (FIV), and use value (UV). Out of the total participants, 50.7% claimed the use of medicinal plants for the treatment of inflammatory conditions such as fever, cough, asthma, swellings, and pain in the joints. A total of 43 medicinal plants belonging to 28 plant families were mentioned, out of which Coriandrum sativum (RFC = 0.23) was the most cited species. The most cited plant family was Fabaceae, and the family importance value was highest in Apiaceae. The majority of the nonusers of the herbal remedies mentioned that they would shift to herbal products if scientific information is available on the efficacy of these products.